2001
DOI: 10.1029/2001gl013020
|View full text |Cite
|
Sign up to set email alerts
|

Seismic facies characterization by monoscale analysis

Abstract: Abstract.Relating sedimentary records to seismic data is a major challenge. By shifting focus to a scale-invariant sharpness characterization for the reflectors, we develop an attribute that can capture and categorize the main reflector features, without being sensitive to amplitudes. Sharpness is defined by a scale exponent, which expresses singularity order and determines the reflection signature/waveform.Local scale exponent estimates are obtained with a new monoscale method. Compared to multiscale wavelet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
1
12
0
2
Order By: Relevance
“…Finally, FWI calls for some sort of regularization that imposes prior information. Because the elastic properties in the earth contain singularities (zero-, first, and fractional-order discontinuities (Herrmann, 2003;Herrmann et al, 2001;Herrmann, 2001)) that trace curved interfaces, this prior information will be in the form of one-norms on wavelet or curvelet coefficients .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, FWI calls for some sort of regularization that imposes prior information. Because the elastic properties in the earth contain singularities (zero-, first, and fractional-order discontinuities (Herrmann, 2003;Herrmann et al, 2001;Herrmann, 2001)) that trace curved interfaces, this prior information will be in the form of one-norms on wavelet or curvelet coefficients .…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we address all of these issues by presenting (i) a parametric representation for reflectors and waveforms that borrows from earlier work by the authors (see e.g. Herrmann et al, 2001;Herrmann, 2005, and the references therein), (ii) a new nonlinear estimation method for the reflector parameters, and (iii) a rock-physical model that generates transitions, consistent with the parametric model proposed by Herrmann and Bernabé (2004) to model mineralogical phase transitions at upper-mantle discontinuities.…”
Section: Introductionmentioning
confidence: 95%
“…Motivated by empirical studies on sedimentary records, Herrmann et al (2001) made the argument that reflectors can be considered as algebraic singularities, parameterized by a scaling exponent determining the transition sharpness. It was shown that this parameterization corresponds to a generalization of zero-or first-order discontinuities towards fractional-order scale-invariant transitions, indexed by a scale exponent.…”
Section: Introductionmentioning
confidence: 99%
“…Knowing these exponents makes it possible to control the asymptotic statistical properties of the structure. Wavelet based estimators have been successfully used for estimating scaling behaviour (Li, 1998;Herrmann, 1997;Herrmann and Stark, 2001;Zaourar et al, 2006a,b). The central properties of self-affine process enable one to establish a scaling relation between wavelet coefficients at different scales from which the spectral exponent can be extracted.…”
Section: Introductionmentioning
confidence: 97%